Capsaicin reactivates hMOF in gastric cancer cells and induces cell growth inhibition. Issue 11 (1st November 2016) - Wang, Fei; Zhao, Jiayao; Liu, Da; Zhao, Tong; Lu, Zeming; Zhu, Lin; Cao, Lingling; Yang, Jiaxing; Jin, Jingji; Cai, Yong
ABSTRACT: Capsaicin (CAP) is the major pungent component of chili pepper and is being evaluated for use against numerous types of tumors. Although CAP is indicated to target multiple signaling pathways, exact mechanisms of how it disturb cancer cell metablism remain obscure. Recent studies revealed Sirtuin 1 (SIRT1) serves as a potential target of CAP in cancer cells, indicating a direct regulation of cancer cell histone acetylation by capsaicin. The present study evaluated the effect of CAP on gastric cancer (GC) cell lines to understand the mechanism of cell growth inhibition. The results showed that CAP could significantly suppress cell growth, while altering histone acetylation in GC cell lines. Further studies found that hMOF, a major histone acetyltranferase for H4K16, is central to CAP-induced epigenetic changes. Reduced hMOF activity was detected in GC tissues, which could be restored by CAP both in vivo and in vitro . These findings revealed an important role of hMOF-mediated histone acetylation in CAP-directed anti-cancer processes, and suggested CAP as a potential drug for use in gastric cancer prevention and therapy.